Peran Strategis Penyuluh Swadaya dalam Paradigma Baru Penyuluhan Pertanian Indonesia - nFN Syahyuti (Forum penelitian Agro Ekonomi, 2014)
EnglishInvolvement of farmers as actors to support extension activities have been underway for a long time with various approaches. In Indonesia, it started from the involvement of Kontak Tani (Advanced Farmers) in Supra Insus era, then farmer to farmer extension at P4S, as well as Penyuluh Swakarsa (Independent Extension Workers)” (in 2004), and the latest is Penyuluh Swadaya (Self-Help Agricultural Extension Workers) since 2008. The existence of self-help farmer extension workers are recognized since the enactment of Law No. 16/2006 on Extension System of Agricultural, Forestry and Fisheries. However, even though it runs nearly 10 years, the development of the role of self-help farmer extension workers is not optimal. This paper is a review of various posts including the recent research on self-help farmer extension workers and it aims to study the potential and problems of self-help farmer extension workers. It shows that the self-help farmer extension workers have a self-help capabilities and distinctive social position and they have to get right role. Appropriate support should be given to self-help farmer extension workers as the agricultural extension worker in the future and it must be distinguished between the government and private extension workers.  IndonesianPelibatan petani sebagai pendukung dan pelaku langsung dalam kegiatan penyuluhan telah berlangsung cukup lama dengan berbagai pendekatan. Di Indonesia, hal ini dimulai dari pelibatan kontak tani pada era Bimas sampai Supra Insus, lalu pendekatan “penyuluhan dari petani ke petani” (farmer to farmer extension) di P4S, serta pengangkatan penyuluh swakarsa (tahun 2004), dan terakhir penyuluh swadaya (sejak tahun 2008). Keberadaan penyuluh swadaya diakui secara resmi semenjak diundangkannya UU No. 16 tahun 2006 tentang Sistem Penyuluhan Pertanian, Kehutanan dan Perikanan. Namun, meskipun sudah berjalan hampir 10 tahun, perkembangan peran penyuluh swadaya belum optimal. Tulisan ini merupakan review dari berbagai tulisan termasuk penelitian tentang penyuluh swadaya terakhir, untuk mempelajari potensi dan permasalahan penyuluh pertanian swadaya saat ini. Ditemukan bahwa penyuluh swadaya memiliki kapabilitas dan posisi sosial yang khas, sehingga batasan perannya mestilah diberikan secara tepat. Dukungan yang tepat harus diberikan kepada penyuluh swadaya sebagai sosok penyuluh pertanian yang strategis di masa mendatang, yang mesti dibedakan dengan penyuluh pemerintah dan penyuluh swasta.